The Importance of Virtual Immersion in the Rapid Prototyping of Industrial Products. Issue 1 (May 2021) - Ghinea, M.; Deac, G.C.; Deac, C.N.; Nita, F.A.
Abstract: The prototype has played a major role in the design of industrial products since the beginning. The series production was never launched until the designers validated the new product by studying in detail a prototype made identical to the ones that would have come out on the tape. Rapid prototyping, especially through 3D Printing, for small and medium-sized products, managed to improve this design phase by the quality of the prototype obtained and by the short times of its realisation. Recently, virtual immersion tends to replace 3D Printing technology (or work together), the prototype made by this technology offering the designer many more features of the designed product. As a concept, Virtual Reality Aided Design (VRAD) significantly reduces production times, costs and especially allows the rapid modification of the prototype, which is impossible to achieve in 3D Printing. Our article presents the study of a Compressed Air Vehicle (CAV) prototype participating in the international academic competition PNEUMOBILE; it is a study carried out by the UPBAIR team of UPB through virtual immersion. We believe that the study can be extended to the prototyping of any industrial product, adding that our CAV prototype is quite simplistic and quite far from the complexity of a series car.